STUDIES ON PHYSICO-CHEMICAL PARAMETERS OF THE TWO LENTIC WATER BODIES OF DISTRICT DHANBAD, JHARKHAND. - KUMARI, SHARMILA; SINHA, SHAILENDRA KUMAR (The Bioscan, 2023)
In the present study an attempt has been made to assess the physico chemical factors of two perennial lentic water bodies viz., Mandal talab and Raja Talab of district Dhanbad, Jharkhand. The evaluation of limnological factors were done during November 2021 to October 2022. A total of seventeen (17) parameters were taken into consideration for analysis. The average value of selected water parameters of Mandal – Raja Talab, the Temperature was 26.4ºC – 27.08ºC, Electrical Conductivity (EC) 822.41-1238.08 µ/cm, Dissolved oxygen (DO) 5.9 – 4.15 mg/L, pH 7.39 – 7.36, Alkalinity 123.08 – 211.4 mg/L, Total Dissolved Solids (TDS) 645.6 – 1049.9 mg/L, Total Suspended solids (TSS) 75.4 – 101.7 mg/L, Biological Oxygen Demand (BOD) 2.9 – 6.05 mg/L, Chemical Oxygen demand (COD) 34.8 – 81.18 mg/L, Total Hardness (TH) 127.6 – 268.2 mg/L, Calcium (Ca+) 37.05 – 76.18 mg/ L, Magnesium (Mg2+) 8.5 – 18.9 mg/L, Sodium (Na+) 35.1 – 78.9 mg/L, Potassium (K+) 25.16 – 69.41 mg/L, Chloride (Cl-) 54.1 – 127.2 mg/L, Nitrate (NO3-) 1.85 – 8.12 mg/L and Phosphate (PO43-) 1.28 – 1.89 mg/L respectively. Pearson’s correlation coefficient values show high significant positive and negative relationship (p<0.05 level).